Estrogen‐related receptor β deletion modulates whole‐body energy balance via estrogen‐related receptor γ and attenuates neuropeptide Y gene expression. Issue 7 (29th January 2013) - Byerly, Mardi S.; Al Salayta, Muhannad; Swanson, Roy D.; Kwon, Kiwook; Peterson, Jonathan M.; Wei, Zhikui; Aja, Susan; Moran, Timothy H.; Blackshaw, Seth; Wong, G. William
Abstract Estrogen‐related receptors (ERRs) α, β and γ are orphan nuclear hormone receptors with no known ligands. Little is known concerning the role of ERRβ in energy homeostasis, as complete ERRβ‐null mice die mid‐gestation. We generated two viable conditional ERRβ‐null mouse models to address its metabolic function. Whole‐body deletion of ERRβ in Sox2‐Cre:ERRβlox/lox mice resulted in major alterations in body composition, metabolic rate, meal patterns and voluntary physical activity levels. Nestin‐Cre:ERRβlox/lox mice exhibited decreased expression of ERRβ in hindbrain neurons, the predominant site of expression, decreased neuropeptide Y (NPY) gene expression in the hindbrain, increased lean body mass, insulin sensitivity, increased energy expenditure, decreased satiety and decreased time between meals. In the absence of ERRβ, increased ERRγ signaling decreased satiety and the duration of time between meals, similar to meal patterns observed for both the Sox2‐Cre:ERRβlox/lox and Nestin‐Cre:ERRβlox/lox strains of mice. Central and/or peripheral ERRγ signaling may modulate these phenotypes by decreasing NPY gene expression. Overall, the relative expression ratio between ERRβ and ERRγ may be important in modulating ingestive behavior, specifically satiety, gene expression, as well as whole‐body energy balance.